Perceived Enablers and Barriers to Optimal Health among Music Students: A Qualitative Study in the Music Conservatoire Setting - Perkins, Rosie; Reid, Helen; Araújo, Liliana S.; Clark, Terry; Williamon, Aaron (Frontiers in Psychology, 2017)
Student health and wellbeing within higher education has been documented as poor in relation to the general population. This is a particular problem among students at music conservatoires, who are studying within a unique educational context that is known to generate both physical and psychological challenges. This article examines how conservatoire students experience health and wellbeing within their institutional context, using a framework from health promotion to focus attention on perceived barriers and enablers to optimal health in relation to three levels: lifestyle, support services, and conservatoire environment. In order to respond to the individuality of students’ experiences, a qualitative approach was taken based on semi-structured interviews with 20 current or recent conservatoire students in the UK. Thematic analysis revealed a complex set of enablers and barriers: (i) lifestyle enablers included value placed on the importance of optimal health and wellbeing for musicians and daily practices to enable this; lifestyle barriers included struggling to maintain healthy lifestyles within the context of musical practice and learning; (ii) support enablers included accessible support sources within and beyond the conservatoire; support barriers included a perceived lack of availability or awareness of appropriate support; (iii) environmental enablers included positive and enjoyable experiences of performance as well as strong relationships and communities; environmental barriers included experiences of comparison and competition, pressure and stress, challenges with negative performance feedback, psychological distress, and perceived overwork. The findings reveal a need for health promotion to focus not only on individuals but also on the daily practices and routines of conservatoires. Additionally, they suggest that continued work is required to embed health and wellbeing support as an integral component of conservatoire education, raising awareness so that all students are fully informed of where, and how, to seek the information or help that they may need. Finally, they indicate a need for more radical scrutiny of the cultures of conservatoires and an assessment of how these can be modified to best optimize students’ health and wellbeing.